2018
DOI: 10.1002/eap.1741
|View full text |Cite
|
Sign up to set email alerts
|

Effects of agriculture and topography on tropical amphibian species and communities

Abstract: Habitat loss is the greatest threat to the persistence of forest-dependent amphibians, but it is not the only factor influencing species occurrences. The composition of the surrounding matrix, structure of stream networks, and topography are also important landscape characteristics influencing amphibian distributions. Tropical forests have high diversity and endemism of amphibians, but little is known about the specific responses of many of these species to landscape features. In this paper, we quantify the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 68 publications
(235 reference statements)
0
24
0
5
Order By: Relevance
“…; Ribeiro et al. ). This procedure can support choosing among distinct recording schedules prior to start PAM.…”
Section: Temporal Samplingmentioning
confidence: 97%
See 1 more Smart Citation
“…; Ribeiro et al. ). This procedure can support choosing among distinct recording schedules prior to start PAM.…”
Section: Temporal Samplingmentioning
confidence: 97%
“…) and flat riparian habitats (Ribeiro et al. ). Therefore, specific spatial arrangements with multiple recorders as random assignments of recorders (Munro et al.…”
Section: Spatial Samplingmentioning
confidence: 99%
“…We calculated the 95% and the 75% posterior credible intervals (CI) for all the parameters. Following other publications (Mata et al., 2014; Ribeiro et al., 2018), we considered that 95% CI not overlapping zero showed a strong effect and that 75% CI not overlapping zero were enough to show the existence of an effect. Consequently, we considered that when the 75% CI overlapped zero, the support from the data was weak to demonstrate an effect.…”
Section: Methodsmentioning
confidence: 98%
“…We calculated the 95% and the 75% posterior credible intervals (CI) for all the parameters. Following other publications (Mata et al, 2014;Ribeiro et al, 2018), we considered that 95% CI not overlapping zero showed a strong effect and that 75% CI not overlapping zero were enough to F I G U R E 2 Representation of the modelling workflow followed in this study to disentangle effects of environment and trophic interactions, as well as explore species associations (lower left pictogram). The workflow has been divided into three sections: arthropod community models (JSDMs; left square), bird community model (JSDM; central-rigth square), which is used to derive the final results (right).…”
Section: Modelling the Bird Communitymentioning
confidence: 99%
“…Contrastingly, during the rainy season, in which physiological stress is less plausible, the activity and distribution of amphibians are frequently affected by factors at the landscape level, such as distance among habitat patches and the type of land use surrounding these patches. These factors influence the distribution of amphibian species, especially when amphibians leave their habitat patch to carry out activities associated with reproduction and dispersal (Moreira, Moura, & Maltchik, 2016; Ribeiro Jr, Siqueira, Brejão, & Zipkin, 2018; Trenham, Koenig, & Shaffer, 2001).…”
Section: Introductionmentioning
confidence: 99%